Input and Processing Factors Affecting Infants’ Vocabulary Size at 19 and 25 Months - Song, Jae Yung; Demuth, Katherine; Morgan, James (Frontiers in Psychology, 2018)
This study examined the relative contributions of three factors to individual differences in vocabulary development: the acoustic quality of mothers’ speech, the quantity of mothers’ speech, and infants’ ability to recognize words. To examine the quality and quantity of mothers’ speech, recordings were collected from 48 mothers when their infants were 17 months old. Infants’ ability to recognize words was gauged by their performance in a perception experiment at 19 months. We examined the relationship between these measures and infants’ vocabulary size at 19 and 25 months. The quantity of mothers’ speech accounted for the greatest amount of variance in infants’ vocabulary size at 19 months; infants’ ability to recognize words followed next. At 25 months, when mothers’ speech alone is presumably no longer the primary input for infants, infants’ ability to recognize words at 19 months was a better predictor of vocabulary size. The acoustic quality of mothers’ speech was not correlated with infants’ vocabulary size at either age. The findings highlight the importance of considering multiple factors that contribute to early word learning, providing a better understanding of the mechanisms underlying the facilitation process.